A novel method for precise implantation of tracheal Y-shaped stent - Ding, Xin-Min; Ding, Yu-An; Duan, Yan-Fang; Chen, Jiao-Yang; Li, Long; Ren, Fang-Ping; Sun, Jie (Frontiers in Medicine, 2024)
Abstract：The tracheal Y-shaped stent is mainly used for the treatment of critical patients with airway stenosis or esophagotracheal fistula near carina. A novel method for precise implantation of Y-shaped tracheal stents was developed using double-lumen endotracheal intubation and flexible bronchoscopy. This approach aims to address the limitations associated with X-ray or rigid bronchoscopy guidance, such as operational difficulties and the risk of inaccurate stent placement leading to implantation failure or suffocation. With this new technique, 13 tracheal Y-shaped stents were successfully implanted. This method shows promise in reducing the complexity of stent implantation and facilitating timely treatment for patients in need.Additionally, it has the potential to update current operating standards and guidelines for this procedure.